A modern view of the lipid hypothesis and the effect of statins on the physiological systems on the human body (literature review) - Popova , T.V.; Rodynskyi , O.G.; Skubytska, L.D.; Rolduhina, M.O.; Mozgunov , O.V. (Medicni Perspektivi, 2025)
The main objective was to determine whether it is always appropriate, according to the lipid hypothesis, to reduce low-density lipoprotein fractions in primary prevention, particularly through the use of statins. Another aim was to update information on the mechanisms of the adverse effects of statins on various physiological systems of the human body. The study analyzed current scientific evidence on the causal relationships between hypercholesterolemia and the risk of cardiovascular diseases (including their impact on patients’ lifespan and quality of life), as well as the consequences of using the most common treatment for this condition – statins. Statins are a group of hypolipidemic drugs whose mechanism of action involves inhibition of the enzyme 3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMG-CoA reductase), which catalyzes the initial and intermediate stages of cholesterol biosynthesis in the liver. These cholesterol-lowering agents, widely known as statins, are heavily promoted not only for secondary but also for primary prevention of cardiovascular disease (CVD), despite their proven side effects, and in some cases, the risks of their use may outweigh the benefits. The analysis showed that the widespread belief that “elevated cholesterol is the primary cause of cardiovascular disease” is limited, while low cholesterol levels may sometimes pose even greater risks to the body. It is known that statins cause mitochondrial dysfunction and act as mevalonate blockers, promote coronary artery calcification, and inhibit the synthesis of vitamin K2. Statins also interfere with the cardioprotective effects of omega-3 fatty acids and contribute to the development of insulin resistance, while their adverse effects can negatively impact various physiological systems. In conclusion, our findings suggest that in certain patient groups (especially those with low or moderate risk), statin prescription remains debatable. Therefore, we believe that the lipid hypothesis has limitations and requires reconsideration, particularly in the context of primary prevention.